Analisis Perawatan Mesin dengan Pendekatan RCM dan MVSM - Dwi Agustina Kurniawati; Muhammad Lutfan Muzaki Muzaki (Jurnal Optimasi Sistem Industri)
Maintenance system at UMKM ED Aluminum Yogyakarta is using preventive and corrective maintenance program, but the implementation of this program still have many problems. The problem occurs because there is no maintenance system program and the company doesn’t have Standard Operational Procedure (SOP) in maintenance to overcome machine failures resulted in the increase of the downtime value. To cope the problems,  in this paper we used application of SOP and appropriate task maintenance selection using Maintenance Value Stream Map (MVSM) method supported by Reliability Centered Maintenance (RCM). Beside task selected among all products that have been produced, there is one machine that gives the biggest profit to the company. The product is feet infusion. Kondia milling machine is one of machines produces the feet infusion that has the longest downtime which was 17,75 hour during January 2016 until October 2016. RCM consist of Failure Mode Effect Analysis (FMEA), Pareto diagram, decision worksheet RCM, whereas the MVSM describes the maintenance activity. Based on Pareto analysis, the critical components on the Kondia milling machine were the magnetic contactor, relay, fuse, cutter, dynamo and bearing. The result of RCM decision worksheet proposed the appropriate action for the critical components cares. The Standard Operational Procedure (SOP) for the maintenance system on the operation of Kondia milling machine are suggested to the company for getting more significant outcome.